Spherical boron nitride/pitch‐based carbon fiber/silicone rubber composites for high thermal conductivity and excellent electromagnetic interference shielding performance. Issue 31 (9th June 2022) - Xie, Jian; Li, Chenjian; Fu, Yuheng; Chen, Zhimin; Wang, Xuelin; Qin, Hongmei; Zhang, Xiaolin; Zhang, Shixian; Wang, Shan; Xiong, Chuanxi; Zhu, Shipeng
Abstract: Composites with high thermal conductivity and excellent electromagnetic interference (EMI) shielding performance are very important for the long‐term stable operation of electronic equipment. In this work, we report a simple and effective method to construct thermally and electrically conductive network pathways by hybridizing pitch‐based carbon fiber (PCF) and spherical boron nitride (s‐BN), in which PCF plays the role in building the framework, and s‐BN acts as a bridge to connect the PCF framework. This can simultaneously enhance the thermal conductivity and EMI shielding efficiency (SE) of silicone rubber (SR) composites. The s‐BN10/PCF20/SR composite could achieve 5.81 W m −1  K −1 of bulk thermal conductivity. The total EMI SE reached 51 dB at the X‐band of 8.2–12.4 GHz. In addition, the s‐BN10/PCF20/SR would have a good heat resistance index (HRI). The tensile strength and elongation at break of the s‐BN10/PCF20/SR were 1.08 MPa and 21.98%, respectively, and its density was only 1.391 g/cm 3 . In brief, this work provides a simple and effective method to fabricate SR composites with light weight, good thermal stability and suitable mechanical properties to be applied in thermal management and EMI shielding of current electronic equipment. Abstract :